On renesting in semi-captive Barnacle Geese - Mitchell, Carl; Black, Jeffrey M; Owen, Myrfyn; West, John (Wildfowl, 1988)
Nests of 116 semi-captive Barnacle Geese in southern England had their clutches removed at various stages of incubation. Within a period of 8 to 35 days 44% renested. Renesting occured most often in older birds that had spent a short time incubating their first clutch. A local photoperiod cycle which is inadequate to cause the geese to become photorefactory, together with a super abundance of food at Slimbridge may influence such renesting.